Analysis of educational strategies to promote coexistance and discipline at pre school level - Chávez Romo, María Concepción (2017)
This work describes the strategies built by some teachers at pre school level in Mexico to face, from their perspective, coexistance and discipline challenges in the classroom. Given they variety of strategies mentioned, they were classified in three groups: restraining, pedagogical and of specialized and psycological care.Some of the interviewed teachers state that their systematic use contributes to thereduction of disruptive behaviors or misbehaving events in the classroom; other express uncertainty regarding the results and therefore they look for specializedsuppot. In this contribution, in addition to describing the group of strategies found, we analyze if through these actions it is feasible to support learning processes in which children are capable to moderate their behavior and exercise their freedom responsibly.